Catalytic conversion of vegetable oil to gasoline - 205418 Abdul Rahman Songip; H. N. M. Ekramul Mahmud; Symposium of Malaysian Chemical Engineers (12th : 1996 : Universiti Kebangsaan Malaysia, Bangi)
51